What is the wind behind the sails to go abroad? Empirical evidence from the mutual fund industry - Gunnar Lang; Henry Schäfer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Specific industry factors determining cross-border business set-up in the European mutual fund industry are analyzed to contribute to the understanding of production specificities in the financial industry. The findings indicate that the decision on where to domicile a fund is not primarily driven by traditional cost factors, such as registration charges and labor costs. Network conditions with respect to the knowledge-based production process of mutual funds and the interaction with regulating authorities such as the approval process embedded in the legal framework and the quality of the workforce in a dense specialized cluster matter most. Differences in such network conditions may allow fund companies to set up more innovative and complex funds in a shorter period of time in one country than in other countries. The findings highlight also that the practitioners agree on such network determinants as being most important.
urn:nbn:de:bsz:180-madoc-333208
Keywords: D22; F36; G15; G28; 330; Mutual Funds; Business Location Decision; Financial Regulation; Networks in Capital Markets